ANALISIS PENERAPAN JOINT AUDIT OLEH DIRJEN BEA CUKAI DAN DIRJEN PAJAK SEBAGAI BENTUK PENGAWASAN SELF ASSESSMENT SYSTEM SERTA UPAYA MENINGKATKAN KUALITAS AUDIT DALAM RANGKA MENGOPTIMALKAN PENERIMAAN NEGARA - Khotimah, Khusnul (Jurnal Akuntansi AKUNESA, 2014)
The importance of taxes for state revenue, makes auditing very important role related to the implementation of self assessment system consequences. But in the process of auditing has been facing problems due to limited access to information between the Direktorat Jenderal Bea Cukai (DJBC) and the Direktorat Pajak (DJP). So that it provides an opportunity auditee can do tax avoidance and tax evasion of such taxes as take advantage of opportunities (loopholes) are both due to limitation sinsynchronize the data audits. The auditee is an importer who has an obligation both on the tax and customs and excise side. To overcome this, a joint policy audit can streamline data exchange audit, due to the joint audit can improve the quality of audits by competent audit evidence produced by the combination of two auditors who have the competence and independencein their fields complementary to conduct joint inspection. So expect the synergy and cooperationis able to further improve tax payer compliance and enforcement of laws taxation, customs and excise. And it?s able to minimize the potential loss of state revenue that occurred during this time.Keywords: Auditing, Self Assessment System, Joint Audit, DJBC, DJP